The study of the ferroelectric properties of lithium-titanium ferrite; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Malyshev A. V. Andrei Vladimirovich; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich; Zarubin A. N. (2015, 2015)
Title screen